A note on regular rings with stable range one - H. V. Chen; A. Y. M. Chin (International Journal of Mathematics and Mathematical Sciences)
It is known that a regular ring has stable range one if and only if it is unit regular. The purpose of this note is to give an independent and more elementary proof of this result.